The Economics of Forest Disturbances Wildfires, Storms, and Invasive Species - Holmes, Thomas P.; Prestemon, Jeffrey P.; Abt, Karen L.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
This book provides a unique, state-of-the-art review of both traditional and emerging themes in the economics of natural forest disturbances. Although natural disturbances such as wildfire, hurricanes and pests have long been recognized as important factors influencing the structure and health of forests, recent and dramatic increases in the costs and damages associated with forest disturbances necessitates a new evaluation of these processes. The authors show that neo-classical economic principles can be integrated with ecosystem analysis and modern econometric methods to uncover the causes and consequences of natural forest disturbances. The chapters encompass modern areas of concern in forest economics and policy, including temporal and spatial dynamics of economic-ecologic systems, risk-reducing mitigation and adaptation strategies, and the valuation of impacts on market and non-market resources. These topics are developed with case studies demonstrating rigorous empirical analysis with a policy-oriented focus. The book is intended for forest policy analysts and decision-makers, risk managers, forest economists and graduate students studying natural resource economics.
The Economics and Ecology of Forest Disturbances -- An Introduction to the Economics of Forest Disturbance -- Forest Economics, Natural Disturbances and the New Ecology -- Forest Disturbance Processes -- Natural Disturbance Production Functions -- Statistical Analysis of Large Wildfires -- The Production of Large and Small Wildfires -- Climatology for Wildfire Management -- Wildland Arson Management -- Valuing the Economic Impacts of Forest Disturbances -- Designing Economic Impact Assessments for USFS Wildfire Programs -- Timber Salvage Economics -- Wildfire and the Economic Value of Wilderness Recreation -- Forest Disturbance Impacts on Residential Property Values -- Contingent Valuation of Fuel Hazard Reduction Treatments -- Decision Making in Response to Forest Disturbances -- Analyzing Trade-Offs Between Fuels Management, Suppression, and Damages from Wildfire -- A Review of State and Local Regulation for Wildfire Mitigation -- Economic Analysis of Federal Wildfire Management Programs -- Incentives and Wildfire Management in the United States -- Forecasting Wildfire Suppression Expenditures for the United States Forest Service -- Toward a Unified Economic Theory of Fire Program Analysis with Strategies for Empirical Modeling -- Economic Aspects of Invasive Forest Pest Management.
Keywords: LIFE SCIENCES; FORESTS AND FORESTRY; ENVIRONMENTAL MANAGEMENT; ECONOMIC POLICY; FARM ECONOMICS; ENVIRONMENTAL ECONOMICS; LIFE SCIENCES; FORESTRY MANAGEMENT; ECONOMIC POLICY; AGRICULTURAL ECONOMICS; ENVIRONMENTAL ECONOMICS; ENVIRONMENTAL MANAGEMENT